Digital Sovereignty in Indonesia-China Trade Relations - Ratih Anggun Puspita; Athor Subroto; Lili Yulyadi Arnakim (Journal of Social Science, 2023)
The China-Indonesia bilateral cooperation relationship has been going on for a long time, including cooperation in the trade sector. In 2019, the signing of the e-SKA data MoU was carried out as a basis for exchanging data for exporters and importers of the two countries. The transformation of the certificate of origin into e-SKA is one of the efforts to keep pace with the increasingly rapid development of technology and digital. Thus, digital developments need to be accompanied by the readiness of the state to have a defense and security system as an effort to maintain and realize digital sovereignty. This research was analyzed with the theory of Competitive Intelligence. The method used is a qualitative method with Content Analysis specifications.